2002
DOI: 10.1021/es020725y
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Risk Analysis of Six Volatile Organic Compounds in California Drinking Water

Abstract: The widespread use and storage of volatile organic compounds (VOCs) in the United States has led to releases of these chemicals into the environment, including groundwater sources of drinking water. Many of these VOCs are commonly found in public drinking water supplies across the nation and are considered by state or federal agencies to be potentially carcinogenic to humans. In this paper, we evaluate the detection frequencies, detected concentrations, and relative cancer risks of six VOCs in drinking water s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 11 publications
4
48
0
Order By: Relevance
“…They observed that it is five times higher than that found in Fortaleza city. The CHCl 3 level in Fortaleza is reasonably higher than other levels found in literature (Kuo et al 1998;Lin and Hoang 2000;Williams et al 2002;Lee et al 2004;Tokmak et al 2004;Uyak 2006). The concentrations of CHBrCl 2 and CHBr 2 Cl measured in our work are also higher than those concentrations found in studies cited above.…”
Section: Thm Concentrations In Tap Water Samplessupporting
confidence: 46%
See 1 more Smart Citation
“…They observed that it is five times higher than that found in Fortaleza city. The CHCl 3 level in Fortaleza is reasonably higher than other levels found in literature (Kuo et al 1998;Lin and Hoang 2000;Williams et al 2002;Lee et al 2004;Tokmak et al 2004;Uyak 2006). The concentrations of CHBrCl 2 and CHBr 2 Cl measured in our work are also higher than those concentrations found in studies cited above.…”
Section: Thm Concentrations In Tap Water Samplessupporting
confidence: 46%
“…Jo et al (2005) measured a CHCl 3 concentration in air inside household of about 0.15% less than in shower stalls, showing CHCl 3 dispersion is very important. Thus, it is necessary to be careful comparing with other studies published in the literature (Williams et al 2002;Lee et al 2004;Tokmak et al 2004;Uyak 2006). Kuo et al (1998) and Lin and Hoang (2000) performed an estimate using the model proposed by Little (1992), which should be more reliable.…”
Section: Cancer Risks and Hazard Indexesmentioning
confidence: 99%
“…BWs of 62% of the participants were between 50 and 70 kg, while the portion of participants with a BW between 70 and 90 kg was 23%. The median and mean BWs for İzmir population were found to be less than the value, 70 kg, suggested by the USEPA and used in the literature (Williams et al, 2002;Lee et al, 2004). Tokmak et al (2004) used BW of 65 kg for females and 72 kg for males for Ankara residents.…”
Section: Body Weightmentioning
confidence: 71%
“…Duration of sampling surveys or periods of monitoring data varied between 2 weeks (Navarro et al, 2007) and 6 years (Williams et al, 2002). In some cases, no information was given regarding the timing or duration of sampling surveys (e.g.…”
Section: Exposure Assessmentmentioning
confidence: 99%